2009
DOI: 10.1080/15250000902839393
|View full text |Cite
|
Sign up to set email alerts
|

Categorical Representation of Facial Expressions in the Infant Brain

Abstract: Categorical perception, demonstrated as reduced discrimination of within-category relative to between-category differences in stimuli, has been found in a variety of perceptual domains in adults. To examine the development of categorical perception in the domain of facial expression processing, we used behavioral and event-related potential (ERP) methods to assess discrimination of within-category (happy-happy) and between-category (happy-sad) differences in facial expressions in 7-month-old infants. Data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 38 publications
(40 reference statements)
8
61
3
Order By: Relevance
“…They found that both groups showed categorical perception for the continua they tested and that early experience of abuse changed identification of the angry expression (i.e., it was overidentified). Leppänen, Richmond, Vogel-Farley, Moulson, and Nelson (2009) found that infants presented with within-and between-category expressions (happy and sad) showed increased looking time in a visual preference task to between-category pairings but not to within-category pairings. Furthermore, they found that event-related potentials differed depending on condition, that is, between or within category.…”
Section: Categorical Perception In Childrenmentioning
confidence: 96%
“…They found that both groups showed categorical perception for the continua they tested and that early experience of abuse changed identification of the angry expression (i.e., it was overidentified). Leppänen, Richmond, Vogel-Farley, Moulson, and Nelson (2009) found that infants presented with within-and between-category expressions (happy and sad) showed increased looking time in a visual preference task to between-category pairings but not to within-category pairings. Furthermore, they found that event-related potentials differed depending on condition, that is, between or within category.…”
Section: Categorical Perception In Childrenmentioning
confidence: 96%
“…However, this is extremely unlikely given that infants younger than 10 months are sensitive to identity and emotion information with across-valence expressions (e.g., Kahana-Kalman & Walker-Andrews, 2001;Schwarzer & Jovanovic, 2010). An alternative possibility is that within-valence expressions, such as anger and disgust, require additional cognitive resources to process (Leppänen et al, 2009) because they carry additional informational value (Peeters & Czapinski, 1990). For infants, this additional information may elicit greater attention and increase cognitive demands (Vaish, Woodward, & Grossmann, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have explored infants' ability to discriminate within-valence, negative expressions such as fear and sadness (Parker & Nelson, 2005) or anger and sadness (Schwartz, Izard, & Ansul, 1985). These facial expressions are perceptually and conceptually similar, making discrimination and categorization tasks challenging (Leppänen, Richmond, Vogel-Farley, Moulson, & Nelson, 2009). Thus, a lack of empirical attention in this area is problematic, considering that four basic-level emotions (Ekman, 1972) are negatively valenced (i.e., sadness, anger, disgust, fear).…”
Section: Introductionmentioning
confidence: 99%
“…Leppänen, Richmond, Vogel-Farley, Moulson, and Nelson (2009) found that in a visual preference task with happy and sad expressions, infants showed increased looking time to the between category pairings but not to within category pairings. Sevenmonth-old infants show evidence of categorical perception along the happy-fear continuum, but only when habituated to a happy face rather than to the fear face (Kotsoni, de Haan, & Johnson, 2001).…”
Section: Categorical Perceptionmentioning
confidence: 97%